PEMBIAYAAN USAHA PERIKANAN TANGKAP DAN MOBILITAS SOSIAL NELAYAN - Masyhuri, (Jurnal Masyarakat dan Budaya, 2015)
This article aims to address the importance of non-formal financial institution role toward the social mobility of fisherman as well as the development of Indonesian small scale fishing sector. This institution can be an individual entrepreneur or financial agent, which provides credit or other stimulus. From qualitative approach, the social mobility of fisherman and the development of fishing is a consequence of economic relations complexity. However, the role of non-formal financial institution is a dominant factor. This institution is important and always needed as far as the formal financial institutions have not been able to provide opportunity for all fishermen to access the capital. The compatibility of formal finance system and socio- economic characteristics of fishermen is an important factor to encourage the increase of formal finance system role in fishery. Keywords: fishery, fisherman’s income, invesment, social mobility